Qualitative Digital Analysis Using SWOT to Identify Relationship Between Leadership and Employee Commitment of Chinese Restaurant in East Java, Indonesia - Dita Rachmawati; Madziatul Churiyah (Jurnal Sistim Informasi dan Teknologi, 2024)
This study attempts to give MSMEs a general understanding of the advantages, disadvantages, opportunities, and dangers that businesses face while developing and putting into practice a strategy. A case study research design was used by researchers to study MSMEs in Xia Dimsum Malang. Both primary and secondary data, including performance reports and questionnaires, are used in the study. To choose the best course of action, use the SWOT analysis to identify your strengths, weaknesses, opportunities, and threats. Based on the findings of the SWOT analysis, Xia Dimsum Malang need a leadership role plan in order to boost employee loyalty.